STRUCTURAL AND FUNCTIONAL MODEL OF FORMATION OF PROFESSIONAL SKILLS OF FUTURE JUNIOR SPECIALIST ECONOMICS - Гаврутенко, Л. А. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2015)
In the article it comes to training future junior specialists of economics in universities I-II level of accreditation. It was found that a significant factor in shaping the future of professional skills of junior specialists in economics is the development of structural and functional model of professional skills, which structures the stages of preparation of the future junior specialists in economics, will improve them and will help define organizational and pedagogical conditions of the process